Dreamweavers - Corre, Fruto; Rodrigo, Nancy Pe; Chiu, Stella (Bookmark, 1999)
The first segment of this documentary on the T'boli tribe of Lake Sebu features three old weavers who show the entire process of weaving tnalak while telling their life stories. The second segment focuses on three young T'boli performers who try to preserve their culture through the Helobung School of Living Traditions and by teaching the traditions of the T'boli to the young.